Consistency of Instructional Strategies in Controlling Students’ Discipline in the Covid-19 Pandemic Era - Astrid Wangsagirindra Pudjastawa; Helmy Bastian (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2021)
Educational Institutions have been closed around the world due the COVID-19 outbreak. This article aims to describe the results of exploring learning strategies applied at SMKN 3 Malang in the era of the COVID-19 pandemic. This Learning Strategy can help run online teaching in schools. The development of this method departs from researchers’ desire to give birth to online teaching methods in the form of qualitative descriptive. Researchers observe and focus fully on students’ disciplinary behavior in the classroom rules and procedures consistently applied by educators during the learning process. Data collection was carried out through observation, interviews, and documentation. The results showed that students showed consistent attitudes in (1) readiness to learn, (2) cooperation, and (3) independence. Several factors influence success in maintaining consistency in implementing the applied learning strategies, among others; asking students to become moderators who accompany the teacher, distribution of tasks and intensive mentoring for each group member and maintaining two-way learning through regular evaluation and reflection